Cultural creative industries or creative (cultural) industries? - Keane, Michael; Zhang, W. (Shanghai Peoples’ Publishing, 2008)
This essay examines changes in the role of cultural policy in Australia during the past two decades, a period that witnessed an increasing division between supporters of publicly-funded arts and those who identified with the economic value of the creative economy. By the end of the decade the term creative industries had become the preferred approach to policy making, even though there is yet no national creative industries policy, such as in New Zealand. The term ’creative industries’ was first coined by Australian Labor Party policy makers in the early 1990s, a period of transition towards greater economic accountability in the arts and cultural industries. The ensuing ’creation nation’ arts policy was influential beyond Australia’ shores. It was the forerunner of international disruptions to the long-held tradition of the arts as special beneficiaries of government support. In this essay we look at the way that cultural policy has subsequently embraced the turn towards enterprise and innovation. We begin with a discussion of the ’arm’s lengths’ model of cultural policy: the facilitator, patron, architect and engineer models. These models demonstrate degrees of government involvement. This four-part separation of powers, while useful, has failed to account for the knowledge economy and in particular the impact of media convergence. We provide a more contemporary four-model division of the cultural and creative industries: the welfare model, the normal model, the growth model and the creative economy model. The intention of this is to argue that government should be involved in making good policy, but that policy ought to encourage and facilitate innovation. We conclude by problematising the division between cultural and creative industries.